Heidegger, Barbaras and Patočka: original event and historicity - Vélez López, Germán Darío (Estudios de Filosofía, 2020)
The multiple hermeneutical tasks that Heidegger undertook at the end of the ontological interpretation of Dasein in Being and time, prevented him from dealing with the problem of the time-movement relationship. However, this analysis requires tracing the relationship between the time of the Dasein and the time of the world in its entirety, so that the occurrence of existence and its inscription in such a world-wide event can be thought. Thus, this article seeks to determine the link between the original temporality and what Heidegger called the original total temporality. A consistent development of this project, linking phenomenology and metaphysics, which Heidegger called “metontology”, can be found in Renaud Barbaras’s L'ouverture du monde. Lecture de Jan Patočka. At the end of our paper, we will present the central theses of this work in relation to the problem of the relationship of the two mentioned time periods, so that a new metaphysics can be envisaged from them.